Childcare use and overweight in Finland: cross‐sectional and retrospective associations among 3‐ and 5‐year‐old children. Issue 2 (8th May 2015) - Lehto, R.; Mäki, P.; Ray, C.; Laatikainen, T.; Roos, E.
Summary: Background: Different types of non‐parental childcare have been found to associate with childhood overweight in several, but not all studies. Studies on the matter are mainly North American. Objectives: The objective of our study was to examine associations between childcare use and overweight in Finland. Methods: The cross‐sectional and partly retrospective data consists of 1683 3‐ and 5‐year‐old children participating in the Child Health Monitoring Development project (LATE‐project) conducted in 2007–2009 in Finland. Children were measured at health check‐ups and information on child's age when entering childcare, the number of childcare places the child has had, current type of childcare (parental, informal, [group] family childcare, childcare centre) and the current amount of childcare (hours) were gathered. Parents' body mass indices, family educational level, family structure, maternal smoking during pregnancy and child's birth weight were treated as covariates. Results: Beginning childcare before age 1 (adjusted model: odds ratio [OR] 2.53, 95% confidence interval [CI] 1.41–4.52) and, for girls only, number of childcare places (adjusted model: OR 1.33, 95% CI 1.11–1.60), were associated with an increased risk of overweight. The current type of childcare or the time currently spent in childcare was not associated with overweight. Conclusion: Beginning childcare before age 1, which is quite rare in Finland, and having attended several childcare places were associated with overweight even when adjusting for family socioeconomic status and other family background variables. The significance of these findings needs to be further studied.